An accelerated hypofractionated radiotherapy regimen in patients after organ-sparing surgery for stages I-IIA breast cancer - I. A. Gladilina; L. Ya. Klepper; Yu. V. Efimkina; I. V. Vysotskaya; A. V. Petrovskiy; O. V. Kozlov; M. V. Chernykh; E. Yu. Voronchikhina; E. S. Makarov; A. V. Ivanova (ABV-press, 2016)
Objective: to assess the results of accelerated hypofractionated radiotherapy and to comparatively analyze it with the standard radiotherapy in patients with stages I-IIA breast cancer (BC) after organ-sparing surgery.Materials and methods. A total of 203 patients with stages I-IIA BC underwent radiotherapy after organ-sparing surgery. A control group of 91 patients received the standard radiotherapy (the single focal dose (SFD) was 2 Gy 5 times a week, 25 fractions; the total focal dose (TFD) was 50 Gy for 5 weeks). A study group of 112 patients had accelerated hypofractionated radiotherapy (SFD 3 Gy 5 times a week, 13 fractions; TFD 39 Gy for 2.3 weeks).Results. Local recurrences were not detected in any patient after the hypofractionated radiotherapy regimen and were diagnosed in 3.3 % of the patients after the standard regimen. There were no statistically significant differences between the groups in 5-year overall and relapsefree survival rates. Further observation revealed a statistically significant difference in 6-year overall survival rates in the study and control groups: 99.1 and 70.4 %, respectively (p ≤ 0.046). The 6-year relapse-free survival rates in patients who had received the accelerated hypo-fractionated radiotherapy regimen were also significantly higher than in those who had the standard radiotherapy regimen: 97.9 and 71.3 %, respectively (p ≤ 0.043). The rate of post-radiation normal tissue damages after the hypofractionated radiotherapy regimen was significantly lower (15.2 %) than that after the standard regimen (27.5 %). Good and excellent cosmetic results of treatment were achieved in most (95.1 %) patients and did not differ in their frequency after different radiotherapy regimens.Conclusion. The accelerated hypofractionated radiotherapy regimen showed a high efficiency and a favorable toxicity profile in patients with stages I-IIA BC.